PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS CANVA DENGAN TEORI BRUNER PADA MATERI BILANGAN 1-20 - Bilbina Sa`adah; Dhiya Sabita Rahmawati; Rika Aprilia; Alfiana Nurussama; Hafiziani Eka Putri (STKIP Subang, 2025)
This study aims to examine the validity and practicality of Canva-based interactive mathematics learning media based on Bruner's theory for numbers 1-20 for first-grade elementary school students. The abstract nature of mathematics often poses a challenge for students, necessitating media that can bridge these concepts through enactive, iconic, and symbolic stages. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were first-grade students at SDN 5 Sindangkasih, Purwakarta. Data collection techniques included expert validation sheets, and user response questionnaires. The results showed that: (1) Media validity by material experts obtained a percentage of 92% and media experts 94.12%, with a total average of 93.06%, categorized as